Cajeput Seedlings Endurances to Various Media Contaminated by Acid Mine Drainage - Irdika Mansur; Aditya Rizkyandana; Priyanto Priyanto (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
Cajeput (Melaleuca cajuputi) is widely used as a post-mining revegetation plant. The addition of organic matter to post-mining land can improve the physical, chemical, and biological conditions of the soil that lead on to increasing growth and endurance of cajeput in polluted land by acid mine drainage. This study aims to analyze the effect of compost mixture media and roasted husk mixture media to endurance and growth of cajeput seedling and also to analyze the effect of acid mine drainage concentration on the endurances of cajeput seedling on various media. This study used a completely randomized design with two factors consisting of acid mine drainage concentration and type of media. The results of this study indicate that the concentration of acid mine drainage has no significant effect on the growth of height, diameter, and number of leaves, also on total wet weight, total dry weight, moisture content, and root length while the type of media used has a significant effect on growth in height, diameter, and the number of leaves. Keywords: acid mine drainage, compost, Melaleuca cajuputi, roasted husk